The consequences of the value-added tax on inequality - Kaisa Alavuotunki; Jukka Pirttilä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The adoption of the value-added tax has arguably been one of the most important tax policy measures worldwide, but is also one of the most heatedly debated. While some argue that the VAT has served as a useful tool to boost government revenue, others claim that it is also a regressive tax, contributing to increased inequality within the developing world. Using newly released high-quality macro data, this paper offers updated estimates of the revenue impacts of the VAT and the first estimates on its consequences on inequality at the macro level. The results from instrumental variable estimations reveal that the revenue consequences of the VAT have not been positive, contrasting results from earlier work. VAT adoption has not led to increased inequality, suggesting that the move to the VAT has not undermined equitable development.
Keywords: H23; O23; 330; tax policy; value-added tax; inequality; developing countries